A multi-country study of bank reputation among customers in Africa: Key antecedents and consequences - Osakwe, Christian Nedu; Ruiz, Belén; Amegbe, Hayford; Chinje, Nathalie B.; Cheah, Jun Hwa; T., Ramayah (Elsevier, 2020)
This paper studies the antecedents related to service quality and the consequences of bank reputation among bank customers in three prominent markets in Africa, the continent on which one of the banking industries with the highest potential in the world is located. The research hypotheses were tested through the use of partial least squares modelling and by employing data collected from almost 1000 retail-banking customers from Ghana (n = 349), Kenya (n = 337), and South Africa (n = 300). An analysis of these data indicates that service quality dimensions, namely service offering appeal and customer care, meaningfully contribute to the strong perceptions customers have of their banks as regards reputation. The positive role of bank reputation in the development of trust and customer loyalty is also validated in this study. Furthermore, the multi-group analysis shows differences among countries in the case of all the relationships analysed, with the exception of the weight of customer care on bank reputation. Finally, the conclusion is reached that bank managers should focus their reputational strategies on improving the competitiveness of their bank products and should consider subtle institutional differences outside the bank's home-country in order to succeed in their internationalization strategies on the continent.